An update of Conditions in the Donkin-Morien Tunnels - R. W. Seedsman (Canadian Institute of Mining, Metallurgy and Petroleum, 2009)
In 1984 and 1985, two 7.6m diameter TBM tunnels were driven from the Donkin-Morien peninsula in Nova Scotia to access the Harbour coal seam. The design of the ground support was based on identifying zones of rock failure through the application of the Hoek Brown failure criterion and the early use of finite element analyses. In 1992, the mining project was abandoned and the tunnels allowed to flood. Monitoring data from the tunnel was subsequently used as a case study in the development of the concepts of brittle rock behaviour. In 2007, the tunnels were pumped out as part of a feasibility study into the reintroduction of longwall mining into the coalfield. There is a good match between observations of the collapse zones in the roof and sides of the tunnel and a simple elastic analysis using brittle parameters, a spalling limit of 5, and a low independent shear modulus. The brittle analyses form the basis of the design for the resupport of the tunnels.